Congratulations! (Cimarron, New Mexico Cimarron Legend, 1993)
Article on the birth of Woodrow and Diana Picks Daughter Kristin Denise Pick.
Newspaper article
Master List Item # 1
File location is in the New Mexico File Cabinets
Keywords: Pick, Woodrow; Pick, Diana; Pick, Anita; Pick Kristin Denise; Colfax County Medical Center; Birth of child; Family; Raton, New Mexico; Cimarron, New Mexico